LATIHAN ENDURANCE MENINGKATKAN KUALITAS HIDUP LEBIH BAIK DARI PADA LATIHAN PERNAFASAN PADA PASIEN PPOK DI BP4 YOGYAKARTA - Siti Khotimah (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2013)
Quality of life is an individual state within the scope of capabilities, limitations, symptoms, and psychosocial natures to function in the desired range of roles in society and feel satisfied with that role. Quality of life of COPD patient’s considered very important because it relates directly to the symptoms experienced. In COPD patients increased work causes shortness of breath so that the patients had decreased quality of life. There has been indication that endurance exercise and breathing exercise improve quality of life in COPD patient. This study was aimed at testing endurance exercise in improving the quality of life of COPD patients. The study is a quasi experiment with pre-test and post-test control group design. The experiment was conducted in BP4 Yogyakarta. The number of samples was 22 patients with COPD who experienced of reducing quality of life. Quality of life in COPD patients measured by SGRQ questionnaires. The number of study subjects were then grouped at random into two groups. Control group one was given diaphragmatic breathing exercise and pursed lip breathing three times a week. Treatment group two was given endurance exercise three times a week. The study was conducted for 12 weeks. SGRQ total value of the data was measured before and after treatment. All data in the analysis using SPSS version 16. Data are destributed normal and homogen, a decrease in the total SGRQ meaningful on breathing exercises and endurance training with a value of p = 0.000 (p <0.05). This means that breathing exercises and endurance exercises at same time can significantly improve the quality of life. The mean total SGRQ values ??after treatment in group one and group two significantly different, where the value of p <0.05, namely p = 0.000, a decrease of group two’s SGRQ total value greater than group one. This means that endurance exercise improves quality of life better than breathing exercises in COPD patients in BP4 Yogyakarta. It is expected to use endurance exercises in patients with COPD who experience mental decline in quality of life.